The Other Self in Free Fall: Anxiety and Automated Tracking Applications - Gutierrez, Christopher (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
Recent scholarship on the rise of automated self-tracking has focused on how technologies such as the Fitbit and applications such as Nike+ demand that the user internalize the logic of contemporary surveillance. These studies emphasize the disciplinary structure of self-tracking – noting that these applications rely on logics of self-control, flexibility and quantification to produce particular neoliberal subjects. Following these readings, this paper considers the central role that anxiety plays in motivating, and maintaining, the subject’s desire to understand the self through automated tracking systems. I will elaborate on this anxiety in three defined sections. Firstly, I will provide a brief overview of the relationship between anxiety and affect developed in both Freud’s and Lacan’s work on anxiety. Secondly, I will consider how the particular aesthetic principles of two applications, the Nike+ running application and the Spire breath monitoring application, afford the production of anxious digital selves by drawing on the emerging digital aesthetic of the free-fall in order to create a simultaneous distanciation and conflation of the embodied self and the digital self. Finally, I will consider how self-tracking applications represent a particular affective loop, fuelled by the subject’s insatiable jouissance, which drives a never-ending anxious attempt to reunite the subject and object. Ultimately, it is from within these practices of digital self-construction that we can most clearly identify both an everyday anxiety of the self and emergent subjectivity and aesthetic of the present.
Keywords: anxiety; affect theory; self-tracking; quantified self; aesthetics